The Effect of Providing Fermented Milk on The Performance of Gallus domesticus - Dalila Fadhila Hidayat; Agus Widodo; Diyantoro Diyantoro; M. Gandul Atik Yuliani (Journal of Applied Veterinary Science And Technology, 2020)
Backgrounds: Broiler chickens are high productivity livestock. To achieve this productivity, many farmers provide feed additives. Fermented milk is one of the feed additives given through drinking water. Providing feed additives, regularly, will affect the performance of these broilers. Purpose: To investigate the potential of providing fermented milk through drinking water on the performance of broiler chickens. Method: Direct observations and perform calculations on several aspects that support the research. Result: After making observations, it was known that there are differences in the starter phase and the finisher phase. The observation was carried out from the age of 0-27 days. Broiler performance determined by the parameters of feed consumption, chicken body weight, and feed conversion. Conclusion: The observation shows an increase in feed consumption. However, in feed conversion and body weight gain instability is caused by physical conditions, temperature, and palatability in each phase of the broiler chickens.